ANALISIS KOMPETENSI SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA PEGAWAI DI KANTOR CAMAT KECAMATAN ILIR TIMUR TIGA KOTA PALEMBANG - Putranto, Heru Adi; Iasha, Citra; Sunarto, Sunarto; Liana, Triya Ade (SENGKUNI Journal (Social Science and Humanities Studies), 2025)
Ilir Timur Tiga District, Palambang City always pays attention to developing the overall competency of its apparatus which can be implemented through the implementation of education and training to increase their knowledge, skills and abilities. What is the Competency of Human Resources in the Ilir Timur Tiga District Office, Palembang City. This research aims to analyze human resource competencies in the Ilir Timur Tiga District Office, Palembang City.Â The research method used by the author is descriptive research with a qualitative approach, the data collection techniques used are observation, interviews, literature study and documentation and the data analysis techniques used are data reduction, data presentation and drawing conclusions.Â Based on research, Human Resource Competency in the Ilir Timur Tiga District Office, Palembang City, is good and quite adequate, and Employee Performance in the Ilir Timur Tiga District Office, Palembang City. The competencies formed include: The quality of employee performance is good enough, the quantity of employee performance is good, responsibilities are carried out according to applicable regulations, cooperation in Ilir Timur Tiga sub-district is good where they do their work by helping each other. Work initiatives have gone well where employees understand and already have work initiatives.